EU Financial Instruments in Practice: SMEs’ investments in energy efficiency and renewable energy in Croatia - Celic, Florijan; Vlahinic Lenz, Nela (International Journal of Energy Economics and Policy, 2022)
In the context of the EU development strategy based on a climate neutral economy by 2050, an important dilemma for policy makers is how to provide an incentive for companies, especially small and medium-sized enterprises (SMEs), to make energy efficiency and renewable energy projects their high priority. The aim of this paper is to provide an independent empirical assessment of EU financial instruments and its barriers, used by SMEs targeting energy efficiency and renewable energy. Ex-Ante evaluation was carried out on a sample of 320 SMEs in Istria County, Croatia. The results of the empirical research suggest that despite of a low interest of investors in green projects, the use of the innovative financial instrument would significantly contribute to an increase in the number and value of investments in energy efficiency and renewables. Similar to most of other studies, our results also confirmed that administrative and bureaucratic barriers are perceived as the biggest obstacle for SMEs. It is therefore necessary to reduce the number of bodies involved, improve the quality of information dissemination and simplify procedures.